FILANTROPI, ZAKAT DAN PEMBERDAYAAN MASYARAKAT: DARI PERUBAHAN SOSIAL KE TRANSFORMASI SOSIAL DI ACEH - Nurdin, Abidin; Djawas, Mursyid; Kiramang, Khairuddin; Alqarni, Wais; Darna, Andi (IAIN BONE, 2025)
Management of zakat, infaq and shadaqah funds through philanthropic movements is not only part of social change but also a social transformation. because the funds given to the community are not just to meet consumptive needs such as living expenses, health costs or incentives alone, but the funds are given in the form of business capital, training, education costs, workshops and life skills and equipment assistance. So that the zakat, infaq and shadaqah funds become productive and effective, and the community is empowered in terms of resources, economy, social and skills. The study used a qualitative method analyzed with the theory of the sociology of religion. Religion can encourage humans to carry out social transformation, namely changes in form in the form of ideas, concepts and practices or practices in a better life. In this study, through religious teachings, it can become a spirit that encourages someone to do good and help others such as paying zakat, infaq and shadaqah.